PROFESIONALISME DAN PRODUKTIVITAS KERJA PEGAWAI DI BAGIAN PEMERINTAHAN SEKRETARIAT DAERAH KABUPATEN MAHAKAM ULU - Florensia Huring (ADMINISTRASI PUBLIK, 2018)
Problems in this study is How Professionalism and Employee Productivity in the Administration Section Regional Secretariat Mahakam Ulu District? This study aims to find out knowing Professionalism and Employee Productivity in the Administration Section Regional Secretariat Mahakam Ulu District.The timing of the research is conducted in December 2017 until May 2018 for 5 (five) months. The research method in this research is descriptive, the data obtained through direct observation to the field and spread the questionnaire to the speakers with the number of samples are 18 (eighteen) respondents.Based on the analysis of the data obtained the average score scores obtained for professional variables is 56.67 / 13 = 4.36 which can be categorized very well and the average score score of work productivity is 52.50 / 12 = 4.38 and categorized very well. So it can be concluded that the professionalism and productivity of employees in the Division of Government Secretariat District Mahakam Ulu is very good.